Endobronchial involvement as an extremely rare manifestation of the Waldenström's disease - Bartáková, Hana; Novák, Jan; Jakša, Radek; Beneš, Jiří; Votruba, Jiří (The clinical respiratory journal, 2018)
Pulmonary infiltration is an infrequent organ involvement in Waldenström's disease (WD). Diffuse infiltration, isolated parenchymatous nodules, and pleural effusion are the most common manifestations of WD, while endobronchial mass is extremely rare. We present a case report of a 66-year-old man with a long-standing history of WD, who developed febrile neutropenia after therapy with rituximab, cyclophosphamide, and dexamethasone. X-ray and CT scan showed consolidation consistent with right-sided pneumonia. Surprisingly, bronchoscopy revealed an endobronchial tumor obstructing the right lower lobe (RLL) and two smaller granulations. Biopsies were obtained and recanalization of the RLL bronchus was performed. Immunohistological staining of the samples was consistent with lymphoplasmacytic lymphoma. Despite the change in therapy the patient died 6 weeks later. A review of published literature revealed only two case reports of endobronchial involvement in WD to this day. While one of the case reports described a patient with diffuse submucosal infiltration of the airways, the other one presented a patient with bronchus-obstructing tumor similar to the case reported here.
Keywords: bronchoskopie; počítačová rentgenová tomografie; kombinovaná terapie; fatální výsledek; Humans; Rare Diseases; Biopsy, Needle; Disease Progression; jehlová biopsie; Aged; Waldenströmova makroglobulinemie; protokoly protinádorové kombinované chemoterapie; nádory průdušek; senioři; lidé; Immunohistochemistry; imunohistochemie; Male; Tomography, X-Ray Computed; Bronchial Neoplasms; Antineoplastic Combined Chemotherapy Protocols; progrese nemoci; Risk Assessment; Combined Modality Therapy; Fatal Outcome; mužské pohlaví; vzácné nemoci; Waldenstrom Macroglobulinemia; hodnocení rizik; Bronchoscopy